NOISE EXPOSURE AND HYPERTENSION - D. Parwizpour; H. Malek-Afzali (Tehran University of Medical Sciences, 1987)
To study the relation between hypertension and noise exposure, after the noise monitoring is weaving and spinning workshops, a especially designed questionnaire was completed and measurement were made of blood pressure, height and weight of 1801 male and female workers employed in these workshops. The results indicated that the systolic and diastolic pressure had a direct relation with age and indirect relation with the pondoral index on the other hand sex had relation with diastolic pressure. Multiple regression analysis was made to eliminate the effect of age, sex and pondoral index. The result showed that the diastolic pressure in weavers were higher than the spinners. This fact probably is due to significant different between noise levels in these workshops. (P